Hyaluronic Acid Nanoporous Microparticles with Long In Vivo Joint Residence Time and Sustained Release. (12th April 2017) - Palmieri, Graziana; Rinaldi, Antonio; Campagnolo, Luisa; Tortora, Mariarosaria; Caso, Maria Federica; Mattei, Maurizio; Notargiacomo, Andrea; Rosato, Nicola; Bottini, Massimo; Cavalieri, Francesca
Abstract : A simple approach is reported to engineer biodegradable and biocompatible nanoporous hyaluronic acid particles (NPHAs) with a characteristic sponge‐like morphology and uniform size. These NPHAs can be synthesized using the concomitant cross‐linking of hyaluronic acid and the cross‐linking agent precipitation. The nanoporous architecture of NPHAs prevents the rapid enzymatic degradation of hyaluronic acid and controls the erosion of microparticles in physiological conditions. Once injected into an intra‐articular body cavity of healthy mice, these NPHAs reside at the point‐of‐delivery for an extended time period, exhibiting a sustained release of hyaluronic acid. In addition, in vivo studies indicate the persistence of NPHAs in the knee joints with neither accumulation into major organs, nor any local or systemic side‐effect. The use of NPHAs is emphasized as reservoirs of hyaluronic acid, effectively providing an innovative and safe platform for prolonging the favorable effects displayed by hyaluronic acid on joints affected by osteoarthritis. Abstract : Hyaluronic acid is assembled into nanoporous particles using the polysaccharide backbone for nucleation and crystallization of the cross‐linking agent. In vivo and in vitro studies demonstrate the remarkable functional properties of these nanoporous particles, highlighting a long persistence time of five weeks in murine joints without eliciting any systemic and local side‐effects or inducing accumulation into major organs.